Evaluación de la implementación del “Centro Gerontológico Diurno Loja”, año 2023. - Guamán González, Natalia Elizabeth (2024)
The general objective of this curricular integration work is to evaluate the implementation of the "Loja Gerontological Day Care Center" in the year 2023, with respect to compliance with the "Technical Standard for the Implementation and Provision of Attention and Care Services for Gerontological Day Care Centers" issued by the Ministry of Economic and Social Inclusion. In order to achieve this purpose, two specific objectives have been set: first, to analyze the implementation of the gerontological center; and second, to contribute to the development of an improvement proposal based on the findings identified. To this purpose, 6 variables were designed according to the parameters established in the Technical Standard, which made it possible to identify and analyze compliance with said standard, and subsequently make a proposal for improvement. The information gathered was obtained from front-line staff, i.e., professionals who interact directly with older adults, and through direct observation of the physical environments. As a result, implementation gaps were identified, such as the lack of a family support plan, literacy programs, differentiated menus, adequate human talent and safe and protective environments. In response to these findings, the strategies proposed in the improvement proposal address the collaboration of academia in the development of the family support plan, the individual assessment of the mobility of older adults, and the implementation of literacy programs. In addition, the acquisition of equipment and the redesign and relocation of the institution's facilities are recommended. In conclusion, this study shows a deficit in the implementation of the Loja Gerontological Day Center. The findings highlight the importance of a constant review of public policy from a bottom-up perspective to ensure that older adults receive comprehensive and adequate care based on their specific needs.